Exploring the efficacy of maternal, child health and nutrition interventions in Uganda - Mbabazi, Muniirah (2017)
Introduction and background: Malnutrition, particularly undernutrition remains a major development challenge for sub-Saharan Africa. There has been mixed progress in reducing undernutrition and the numbers remain unacceptably high. However, high impact nutrition interventions have been recommended for implementation in high burden malnutrition countries to address undernutrition. Countries have responded by designing policies and programmes that reflect these recommendations. However, there is limited evidence of what works and how in local contexts. Objectives: This research explored the efficacy of nutrition interventions and modality of delivery of interventions and programmes in Uganda at national, local government and community levels. Specifically this study examined key stakeholders’ experiences of current nutrition interventions at district level in Uganda; assessed the effectiveness of previous nutrition specific and nutrition sensitive interventions on maternal and child health outcomes in Uganda; and examined the relationship between socio demographic and health factors on nutrition outcomes in Uganda. Methods and subjects: Using a combination of methods (mixed methods), this study explored nutrition interventions targeting mothers of reproductive age and children (0-5 years) in three separate studies. A systematic review was conducted to explore existing evidence on the nature of maternal and child health and nutrition interventions; and methods used to deliver them since 1986-2014. Studies were included if they were done in Uganda and reported health and nutrition related outcomes among the study group. Included studies were assessed for quality using the Newcastle Ottawa Scale. Twenty-two predominantly cross-sectional and longitudinal studies were included in the review. A qualitative study covering project implementers and project beneficiaries (n=85) in local communities was conducted using face-to-face interviews. Interviews explored methods used to deliver interventions and implementers’ and community participants’ perspectives and experiences of on-going nutrition interventions at local government (LG) and community level. Community beneficiaries were mothers or caretakers of children aged 0-59 months accessing interventions from two studied projects, while implementers were project staffs or health workers on the same projects. Interviews were transcribed verbatim and thematically analysed. Population based data of the 2011 Uganda demographic and health Survey (DHS) was quantitatively analysed. Logistic regressions analyses were done to establish factors that influence child stunting and anaemia in Uganda. Models were constructed based on 2350 stunted and 2056 child anaemia cases in the data set. Using a multilevel model design of mixed methods research, findings from each study were triangulated to obtain complementary information on the study phenomena. Results: Results suggest that planning and implementation of nutrition interventions in Uganda has transformed from random to systematic implementation since 1986. Nutrition interventions delivered diverse activities to address multiple causes of undernutrition in Uganda. However, activities were predominantly non-integrated delivered specifically at facilities or in communities. Methods of delivering interventions were broad to include community and health system compatible strategies (community mobilisation, outreaches and individual or group nutrition education and counselling) to prevent, manage and treat undernourished cases at facilities and within communities. Results further showed that maternal anaemia status, age of child and geographic factors were associated with stunting and anaemia in children. Further, the qualitative study showed, there was a conducive policy environment to implement multi-sectoral nutrition interventions in Uganda. There were linkages, collaborations and partnerships to delivery multi-sectoral integrated nutrition actions in communities and LG. Results however reveal that the dominance of external partners in implementing nutrition interventions; and absence of functional coordinating structures and mechanisms hinders intervention scale up. Further there was a need to address system and community barriers that affect implementation to improve nutrition outcomes and scale up at LG and community level. Conclusion: There have been great strides towards solving challenges of malnutrition in Uganda. Integrated approaches using community mobilisation and nutrition education and counselling at health facilities were among common delivery methods. However, bottlenecks exist in prioritisation and commitment to scale. There is a need to strengthen integrated approaches to delivering interventions across the LG and communities for multi-sectoral programming and implementation to reduce the number of undernourished Ugandans.